(untitled) (Web of Teachers: Inderscience Research, 2026)
This article provides a comprehensive overview of the anatomical structure of the human skull, its main sections and functional significance. The division of the skull into the cranial and facial skeletons, the location and functions of the bones included in these parts are described in detail. The types of joints of the skull bones, their stages of development and their biological and physiological significance in human life are also analyzed. The article highlights the role of the skull in protecting the brain and sensory organs, its participation in the processes of chewing, breathing and speech formation. This material serves as a theoretical resource for students studying anatomy, teachers and students of medicine and biology.